Learner Agency, Motive, and Self-Regulated Learning in an Online ESL Writing Class - Zhang, Jie (IALLT Journal of Language Learning Technologies, 2013)
Online learning has become a viable popular alternative to traditional ESL writing classes over the past decade. However, the effectiveness and validity of online ESL learning remains controversial. Furthermore, most researchers have used surveys to assess student perceptions of online learning. This study presents a case study of two participants in an online ESL writing course at a university in the Northeastern United States. Using activity theory as a framework, I explore what makes a successful learner in an online environment and how learner agency, motive, and self-regulation impact student performance and academic achievement in the online learning context. Data from different sources were collected to provide a triangulated analysis. Results suggest that learners who employ good self-regulation strategies and are motivated to learn and adapt tend to benefit more from the online learning experience, while students who do not employ such strategies and are motivated solely to fulfill a degree requirement are more likely to be frustrated. The results also reveal that the physical distance created by technology could be a challenge for those who do not seek assistance from instructors or peers. In other words, learners need guidance and support on how to be self-motivated and self-directed in the online environment. I also discuss how to effectively design and deliver an online ESL course.